Salivary irisin level is higher and related with interleukin-6 in generalized periodontitis - Türkmen, Emrah; Uzun, Erdem Veli; Bozaba, Fuat; Balcı, Nur; Toygar, Hilal (Springer Science and Business Media Deutschland GmbH, 2023)
Objectives: Irisin plays an important role in energy homeostasis, inflammation, glucose, and lipid metabolism, and it is shown to have relations with many inflammatory diseases. The aim of the study was to determine saliva and serum irisin and IL-6 levels in patients with stage III/grade B periodontitis compared with individuals with healthy periodontium. Materials and methods: Twenty patients with stage III grade B periodontitis (P) and 20 periodontally healthy subjects (control; C) were included in this study. Clinical periodontal measurements were recorded. Saliva and serum levels of irisin and interleukin-6 (IL-6) were analyzed by enzyme-linked immunosorbent assay. Results: Salivary irisin and IL-6 levels were significantly higher in the periodontitis group (p < 0.001, p = 0.002, respectively). Furthermore, serum IL-6 levels were found significantly higher in the periodontitis group compared with controls (p = 0.011). There was no significant difference between the periodontitis and control for serum irisin levels (p > 0.05). Significant positive correlations were found between all periodontal parameters and salivary irisin and IL-6 (p < 0.05) and also between BMI and saliva and serum IL-6 (respectively; r = 0.530, r = 0.329, p < 0.05). There was a positive correlation between salivary irisin and IL-6 (r = 0.369, p < 0.05). Conclusions: Monitoring of salivary irisin and IL-6 might be potential biomarker for predicting the susceptibility to periodontitis. Clinical relevance: Scientific rationale for the study: Irisin is a novel adipomyokine that has played an important role in energy homeostasis, glucose and lipid metabolism, angiogenesis, immunity, and inflammation. Irisin is involved in the pathogenesis of diseases affecting many body systems. IL-6, another adipomyokine, is a major inflammatory mediator and homeostatic regulator of glucose and lipid metabolism and is associated with periodontitis. No studies investigated the relationship between advanced periodontal disease, irisin, and IL-6 together. Principal findings: The salivary irisin and IL-6 levels were significantly higher and positively correlated in patients with periodontitis relative to healthy controls. Furthermore, serum IL-6 levels were significantly increased in patients with periodontitis. Practical implications: The study shows that irisin and IL-6 can be candidate salivary biomarkers for periodontitis and predict to periodontal status.
Keywords: IL-6; Irisin; Periodontitis; Saliva